(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2026)
This case highlights the forensic importance of identifying injuries in cases of prolonged vehicular dragging. A 27-year-old male motorcyclist died after being trapped under a speeding limousine and dragged for nearly 11 km. The Re-postmortem revealed extensive abraded lacerations, deep soft tissue loss, and exposed bones with characteristics of “grinding/friction” injuries. Vital reaction was found in wounds over the body. Internal findings showed craniocerebral injuries and long bone fractures. These injury patterns helped to reconstruct the incident as a possible manslaughter or homicide. This case highlights the medicolegal significance of re-postmortem examination in clarifying manner of death in complex vehicular dragging incidents.